2012
DOI: 10.1159/000330896
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Endotoxin Tolerance Protects against Cockroach Allergen-Induced Asthma-Like Inflammation in a Mouse Model

Abstract: Background: Compounds which activate the innate immune system, such as lipopolysaccharide, are significant components of ambient air, and extremely difficult to remove from the environment. It is currently unclear how prior inhalation of endotoxin affects allergen sensitization. We examined whether lung-specific endotoxin tolerance induction prior to sensitization can modulate the response to allergen. Methods: Endotoxin tolerance was induced by repeated intratracheal exposure to endotoxin. All mice were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…sensitisation with LPS-contaminated OVA, the observed airway inflammation was dependent on IL-17 [39]. In addition, it has been reported that tolerisation to LPS prior to sensitisation can prevent eosinophilic infiltration in BAL [40]. It is thus likely that LPS, or other constituents of the CDE, promote the mixed type of airway response seen in our cat allergen-induced asthma model.…”
Section: Discussionmentioning
confidence: 80%
“…sensitisation with LPS-contaminated OVA, the observed airway inflammation was dependent on IL-17 [39]. In addition, it has been reported that tolerisation to LPS prior to sensitisation can prevent eosinophilic infiltration in BAL [40]. It is thus likely that LPS, or other constituents of the CDE, promote the mixed type of airway response seen in our cat allergen-induced asthma model.…”
Section: Discussionmentioning
confidence: 80%
“…Increased endotoxin concentrations were found in the house dust of farms compared to urban environments, suggesting a protective effect against the development of atopy [50], possibly by causing Th1 domination in the immune system [51,52]. However, this protective effect of the farm environment may exist only in the early years of childhood [53].…”
Section: Bacterial Lps/bacterial Endotoxinmentioning
confidence: 99%
“…However, this protective effect of the farm environment may exist only in the early years of childhood [53]. In a mouse model, pulmonary endotoxin tolerance was found to be protective against cockroach allergen-induced asthma-like inflammation [52]. Obesity was found to be associated with the development of atopic dermatitis only in children.…”
Section: Bacterial Lps/bacterial Endotoxinmentioning
confidence: 99%
“…Shi et al studied leukocyte distribution in the BAL fluid using aerosolized OVA-challenged mice and they found that the number of inflammatory cells was markedly reduced by persistent or intermittent OVA challenges, which was related to the development of allergen-dependent immune tolerance. Natarajan et al used LPS to induce long-lasting immune tolerance in mice, and they found lessened inflammation associated with asthma caused by cockroach allergens [8]. …”
Section: Discussionmentioning
confidence: 99%